A 2D-proteomic analysis identifies proteins differentially regulated by two different dengue virus serotypes - Chanida Chumchanchira; Suwipa Ramphan; Atchara Paemanee; Sittiruk Roytrakul; Pathrapol Lithanatudom; Duncan R. Smith (Scientific Reports, 2024)
Abstract The mosquito transmitted dengue virus (DENV) is a major public health problem in many tropical and sub-tropical countries around the world. Both vaccine development and drug development are complex as the species Dengue virus consist of four distinct viruses (DENV 1 to DENV 4) each of which is composed of multiple lineages and strains. To understand the interaction of DENV with the host cell machinery, several studies have undertaken in vitro proteomic analysis of different cell lines infected with DENV. Invariably, these studies have utilized DENV 2. In this study we sought to define proteins that are differentially regulated by two different DENVs, DENV 2 and DENV 4. A 2-dimensional proteomic analysis identified some 300 protein spots, of which only 11 showed differential expression by both DENVs. Of these, only six were coordinately regulated. One protein, prohibitin 1 (PHB1) was downregulated by infection with both DENVs. Overexpression of PHB1 increased DENV protein expression, level of infection and genome copy number. DENV E protein colocalized with PHB, and there was a direct interaction between DENV 2 E protein and PHB1, but not between DENV 4 E protein and PHB1. The low number of proteins showing coordinate regulation after infection by different DENVs is a cause for concern, particularly in determining new druggable targets, and suggests that studies should routinely investigate multiple DENVs.